MANAJEMEN PRAKTIK CIRCULAR ECONOMY PADA PERUSAHAAN MANUFAKTUR DAN FASHION - Bahdin Nur Tanjung; Melisa Nur Asima Sidabutar; Dewi Sartika Situmorang (Jurnal Industri Kreatif dan Inovatif, 2025)
This article examines the management practices of circular economy in companies within the manufacturing and fashion sectors. Circular economy is presented as an alternative to the traditional linear production model (“take–make–use–dispose”), which typically leads to high waste generation and inefficient resource consumption. The study aims to identify and describe existing practices, analyze implementation challenges (including operational, financial, regulatory, and consumer perception aspects), and review adaptive solutions and strategies that companies can adopt. Using a qualitative approach with a systematic literature review, the article finds that the transition to a circular economy is shaped by factors such as consumer awareness, production and operational costs, and policy support. In manufacturing, a shift toward servitisation/Product-as-a-Service (PaaS), the application of circular design (e.g., value hill), and cross-supply-chain collaboration—often enabled by digital technologies (IoT, sensors, traceability)—are highlighted. In fashion, circular practices include rental models, resale/recommerce, and repair programs that emphasize durability and repairability to move away from fast fashion. Key challenges include high initial investment costs, inconsistent regulatory support, changes in consumer behavior, and the need for close coordination among supply-chain stakeholders. The article offers strategic recommendations for industry players and policymakers to support a more effective transition toward circular economy.